Radical prostatectomy versus radiotherapy as local therapy for primary tumors in patients with oligometastatic prostate cancer - Ham, Won Sik; Park, Jee Soo; Jang, Won Sik; Kim, Jongchan (Frontiers in Oncology, 2024)
We compared radical prostatectomy (RP) and radiotherapy (RT) as local therapies for primary tumors and examined their associations with survival outcomes and urinary tract complications in patients with oligometastatic prostate cancer (omPC). We evaluated the data of 85 patients diagnosed with omPC who underwent local therapy for primary tumors between January 2008 and December 2018.Of the 85 patients, 31 underwent prostate RT, while 54 underwent RP. Oligometastatic disease was defined as the presence of fewer than five metastatic lesions without visceral metastasis. Urinary tract complications, progression-free survival (PFS), cancer-specific survival (CSS), and overall survival (OS) were evaluated using the Kaplan-Meier method and Cox regression analyses. Patients treated with RT showed higher prostate-specific antigen levels. There was no significant difference in the 5year PFS (52.5% vs. 37.9%, p=0.351), CSS (67.6% vs. 84.7%, p=0.473), or OS (63.6% vs. 73.8%, p=0.897) between the RT and RP groups. In the multivariate analyses, the type of local therapy was not associated with PFS (hazard ratio [HR]=1.334, p=0.356), CSS (HR=0.744, p=0.475), or OS (HR=0.953, p=0.897). Therefore, RP seems to be a suitable treatment option for patients with omPC, exhibiting oncologic outcomes comparable to those with RT.